Lean: a continuous improvement philosophy in agile systems based on quality management principles. (1st January 2012) - Dibia, Ifechukwude K.; Dhakal, Hom Nath; Onuh, Spencer
The lean philosophy is based on optimisation through continuous improvement and absolute waste minimisation by factual analysis, just-in-time (JIT) in material sourcing, production and delivery to customer, total preventive maintenance (TPM), total quality management (TQM) and strategic competitive human resource management (HRM). These are lean practices which have spanned decades and centuries in one form or another, under countless innovative concepts aimed at attaining superior performance and quality at a lower cost that guarantees strategic competitive advantage. This paper takes a comparative look at the lean philosophy and the quality management principles from the leadership, people, process and outcome perspective.